STRATEGIES IN LEARNING SPEAKING SKILLS USED BY THE ADULT EFL STUDENTS - Pratiwi Samad; Wira Kafryawan (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2021)
This research was conducted to find out and to describe the speaking skills strategies used by the adult EFL students of Pohuwato University and the adults' reason for using those strategies in learning speaking skills. The qualitative descriptive has been employed as the method of the research, and the researcher took the students in the fourth semester of the English department of Pohuwato University as the subject of the research through purposive sampling. To obtain the data, the researcher used the interview and observation as the instrument. The result of the data shows that there are three strategies used by adult EFL students in learning speaking skills. They are cognitive, metacognitive and socio-affective strategies. In cognitive strategy, the students mostly like to apply practicing and analyzing and reasoning. In metacognitive, they used to apply arranging and planning and monitoring, and in socio-affective, they applied to cooperate with others as their strategies to use in learning speaking skills.